Types and Multiplicity of Solutions to Sturm–Liouville Boundary Value Problem - Dobkevich, Maria; Sadyrbaev, Felix (Mathematical Modelling and Analysis, 2015)
We consider the second-order nonlinear boundary value problems (BVPs) with Sturm–Liouville boundary conditions. We define types of solutions and show that if there exist solutions of different types then there exist intermediate solutions also.